Disagreeing before acting: The paradoxes of critique and politics from Adorno to Rancière - Cachopo, João Pedro (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2013)
This article develops the hypothesis that the paradoxical character of critique (the fact that it questions its own grounds) is not an obstacle to, but a condition of, its theoretical and practical effectiveness. In order to clarify and expand this hypothesis with regard to its political implications I examine Rancière’s distinction between “politics” and “police,” his appraisal of “disagreement” (in contrast to Lyotard’s “différend”), along with his thesis that the rationality of “disagreement” sheds light on the paradox of politics (which consists, to paraphrase Rancière, in the very absence of any ground for the power of ruling). This will help counter the well-known criticism raised by Habermas against Adorno according to which a non-normative understanding of critique entails a “performative contradiction.” Against this assumption, I argue that to foster “disagreement” over what constitutes politics, in order to stimulate new ways of imagining what might be done – rather than to promote “consensus” on what should be done – is hardly an inappropriate goal for a politically focused philosophical critique.